Early Clinical and Electrophysiological Brain Dysfunction Is Associated With ICU Outcomes in COVID-19 Critically Ill Patients With Acute Respiratory Distress Syndrome: A Prospective Bicentric Observational Study*. Issue 7 (9th February 2022) - Benghanem, Sarah; Cariou, Alain; Diehl, Jean-Luc; Marchi, Angela; Charpentier, Julien; Augy, Jean-Loup; Hauw-Berlemont, Caroline; Gavaret, Martine; Pène, Frédéric; Mira, Jean-Paul; Sharshar, Tarek; Hermann, Bertrand
Abstract : OBJECTIVES: Describe the prevalence of acute cerebral dysfunction and assess the prognostic value of an early clinical and electroencephalography (EEG) assessment in ICU COVID-19 patients. DESIGN: Prospective observational study. SETTING: Two tertiary critical care units in Paris, France, between April and December 2020. PATIENTS: Adult critically ill patients with COVID-19 acute respiratory distress syndrome. INTERVENTIONS: Neurologic examination and EEG at two time points during the ICU stay, first under sedation and second 4–7 days after sedation discontinuation. MEASUREMENTS AND MAIN RESULTS: Association of EEG abnormalities (background reactivity, continuity, dominant frequency, and presence of paroxystic discharges) with day-28 mortality and neurologic outcomes (coma and delirium recovery). Fifty-two patients were included, mostly male (81%), median (interquartile range) age 68 years (56–74 yr). Delayed awakening was present in 68% of patients (median awakening time of 5 d [2–16 d]) and delirium in 74% of patients who awoke from coma (62% of mixed delirium, median duration of 5 d [3–8 d]). First, EEG background was slowed in the theta-delta range in 48 (93%) patients, discontinuous in 25 patients (48%), and nonreactive in 17 patients (33%). Bifrontal slow waves were observed in 17 patients (33%). Early nonreactive EEG was associated with lower day-28 ventilator-free days (0 vs 16; p = 0.025), coma-free days (6 vs 22; p = 0.006), delirium-free days (0 vs 17; p = 0.006), and higher mortality (41% vs 11%; p = 0.027), whereas discontinuous background was associated with lower ventilator-free days (0 vs 17; p = 0.010), coma-free days (1 vs 22; p < 0.001), delirium-free days (0 vs 17; p = 0.001), and higher mortality (40% vs 4%; p = 0.001), independently of sedation and analgesia. CONCLUSIONS: Clinical and neurophysiologic cerebral dysfunction is frequent in COVID-19 ARDS patients. Early severe EEG abnormalities with nonreactive and/or discontinuous background activity are associated with delayed awakening, delirium, and day-28 mortality.